Moderasi Beragama Berbasis Kearifan Lokal Suku Pakpak-Aceh Singkil - Erman Sepniagus Saragih (Sekolah Tinggi Teologi Berita Hidup, 2022)
The destruction of the church in Aceh Singkil in 2015 was phenomenal and a fact of the struggle to achieve religious moderation. The Aliansi Pemuda dan Pembela Islam (APPI) demands a firm stance from the local government to crack down on church buildings that do not have a Building Construction Law (IMB). Of course, the church community in Aceh Singkil is not indifferent to the rules and it seems as if the fulfilment of the IMB is a paradigm for the actualization of religious harmony that goes beyond the virtue of local humanism of the local community. This paper argues that even though the fulfilment of IMB is necessary, local wisdom is a “treasure” that cannot be insulted based on any policy because local wisdom can be a medium to create harmony in religious differences. The case of the destruction of the church in Aceh Singkil has certainly become a public study, but there has been no offer related to local wisdom as a basis for being moderate. The conclusions are: First, a community that emphasizes customs needs each other and maintains existing virtues that have been instilled since ancient times is virtuous. Second, simplicity, certainty, and virtue are the basis. Third, open communication by way of kinship is the openness of the philosophical schools of traditional society. If religious ideas carry a message of benefit to the wider community, of course, suspicion will be low, fanaticism will become open, extremists will become dialogical, and be radical virtue.